Circular business models in the European manufacturing industry: A multiple case study analysis. (20th November 2020) - Urbinati, Andrea; Rosa, Paolo; Sassanelli, Claudio; Chiaroni, Davide; Terzi, Sergio
Abstract: Circular economy has recently emerged as an alternative industrial paradigm to the traditional "take, make, dispose" economic model, with the aim to promote more sustainable resource consumption patterns and production processes. However, more empirical research is needed to address the topic of how circular economy is adopted in practice by companies. In this study, we mainly adopt the lenses of circular business models and analyze three European case studies operating in the manufacturing industry that embraced circular economy principles in their business. In particular, the paper investigates and presents peculiar managerial practices to create and capture value in circular business models, and highlights the need to conceive a systemic perspective on the implementation of these practices, especially for companies operating in the manufacturing industry. Moreover, the paper shows to managers willing to embrace circular economy principles how the implementation of managerial practices for circularity can support the design of the manufacturing companies' business model within which they operate. Finally, the paper argues about the role of a peculiar external condition, i.e., the environmental regulation, in influencing the way companies implement the managerial practices for circularity.